The Meaning and Implementation of Green Accounting by Hospital Management: A Phenomenological Study at Labuang Baji Regional General Hospital, Makassar - Saputra, Andi Rafiyadi Eka; Alimuddin, Alimuddin; Said, Darwis (Amkop Management Accounting Review (AMAR), 2025)
This study seeks to observe the conception and application of green accounting as interpreted and applied by executives at Labuang Baji Regional General Hospital in Makassar. The methodological approach adopted is Moustakas' transcendental phenomenology, with data collection facilitated through in-depth interviews, participatory observation, and document review. There were six key participants in this investigation, namely the director, head of the finance division, head of facilities, medical waste administrator, environment/CSR coordinator, and internal auditor. Data analysis was carried out through a series of stages, including epoché, phenomenological reduction, imaginative variation, and essential synthesis. The results of the study show three main findings: (1) green accounting is interpreted as an expression of the hospital's moral, professional, and social responsibility in maintaining environmental sustainability; (2) the implementation of green accounting is reflected in environmental cost recording activities, medical waste management, and energy efficiency efforts, although it has not been fully integrated into the formal reporting system; (3) the application of green accounting faces obstacles in the form of a lack of technical regulations, limited human resources, and the absence of a sustainability unit that is structurally responsible for environmental issues. This study contributes to the literature on environmental accounting in the health sector in Indonesia and recommends establishing a sustainability unit, strengthening employees' technical capacity, and developing environmental reporting guidelines for public hospitals.